Documents and detachment in the figurational sociology of sport - Paddy Dolan; John Connolly (EMPIRIA: Revista de Metodología de Ciencias Sociales, 2015)
This article discusses the methodological implications of using a figurational approach to the study of Gaelic games (the Irish sports of hurling and Gaelic football) and their organisation and governance from the late nineteenth century onwards. Following Norbert Elias, we argue that data generation guided by theories, and potentially modifying such theories, are essential components of research endeavours. The problem of generalisation or representativeness of historical documents can be addressed by treating documents as part of a fi guration of evidence, thereby constituting a mutually supporting network of data that serves as a scaffold or structure for theoretical and empirical findings. Based on the experience of using documents such as newspaper and referee reports of matches, and also organisational documents such as the minutes of meetings at various levels of governance, we contribute to the discussion concerning borders and boundary maintenance between history, sociology and historical sociology. While we elaborate on the Eliasian perspective on emotional detachment, and secondary involvement, when conducting research, we also note the dificulties in avoiding ‘preferred’ readings of national history given that Gaelic games have been intertwined with the narrative and project of national self-determination in Ireland. Researchers are compelled to recognise the theoretical significance of sports as a motor and symbol of emotional identifications, but must also create distance from their own national habitus in order to prioritise participation in intergenerational knowledge generation over further national myth-making.